Test J.M.G. - Garcia, J. M.
I would like to present a specific test for Judo, that we practice in Spain. With this test, we prepare our competitors. They are World Champion (Isabel Fernandez), silver medal in World Championship in Paris (Sara Alvarez), and bronze medal (Raquel Barrientos). Spain had five medals in the last European Championship, and we have six new University world champions in Praha (Czech Republic). The test is composed of three exercises, each lasting one minute (total three minutes). The aim of the test is to measure force resistance in terms of speed under the condition of obtaining a mixture of aerobic/anaerobic energy. The test subject must try to execute the highest number of repetitions possible of each exercise without rest between one exercise and another.